Study the Effect of Chemical Reaction and Magnetic Field on Free Convection Boundary Layer Flow of Heat and Mass Transfer with Variable Prandtl Number - Alam, M. S.; Ali, M.; Alim, M. A. (Journal of Scientific Research, 2016)
The present problem is focused on the free convection heat and mass transfer flow of an electrically conducting incompressible viscous fluid about a semi-infinite vertical plate by the effect of chemical reaction and magnetic field under the action of heat absorption and variable Prandtl nnumber. The governing partial differential equations are transformed to ordinary differential equation by applying local similarity transformation. Then the dimensionless ordinary differential equations are solved using shooting iteration technique along with Runge-Kutta integration scheme. The effects of magnetic parameter and chemical reaction parameter with variable Prandtl number on velocity, temperature and concentration profiles are discussed numerically and shown graphically. Therefore, the results of velocity field decreases for increasing values of magnetic parameter and chemical reaction parameter in both air and salt water. The temperature field decreases in the presence of magnetic parameter but increases for chemical reaction parameter in case of air and salt water. Also, the concentration profile is slightly increased for increasing the values of magnetic parameter but significant decreasing effect are observed for reaction parameter. Finally, the numerical values of the shear stress, rate of temperature and rate of concentration are also shown in a tabular form.